THE FINANCIAL IMPLICATIONS OF BODABODA TRANSPORT BUSINESS AMONG YOUTHS IN ARUSHA- COST BENEFIT ANALYSIS: COST BENEFIT ANALYSISI - Luvinga, Kepha; Kilasara, Simon (Advances in Social Sciences Research Journal, 2020)
ABSTRACT This study reports upon the findings on the cost and profitability of bodaboda transport business among youths in Arusha. As used in this study, the term bodaboda applies for a two wheeled motorized taxi which provides ‘for hire’ type transport services to passengers and goods. The bodaboda have became an employment opportunity to many unskilled urban labour and further job opportunity to informal sector workers who wish to switch jobs in search of higher rewards. The questionnaires were used to collect data to 90 respondents from two districts of Arusha region namely Arusha and Meru district. Data analysis was done using descriptive statistics and cost benefit analysis. The finding from the study indicates that the bodaboda transport business is profitable with the benefit cost ratio (BCR) of 2.8 and the net present value (NPV) of 8,494,920Tsh for five years project duration. By having the benefit cost ratio and the net present value greater than 1, the bodaboda business is profitable and worth being undertaken. Based on the findings from the study it is recommended that the government authorities and all key stakeholders should regulate, and support the implementation of bodaboda bussiness through formalization of bodaboda associations, assurance of financial supports and capacity building to youths who engage or willing to engage in the business.